The characterizations of the curves in a 3-dimensional lightlike cone - Bektaş, Mehmet; Külahci, Mihriban; Yilmaz, Münevver Yildirim (Walailak University, 2015)
In this paper, m-curvature functions are defined for curves in a 3-dimensional null cone. Furthermore, a new characterization is given for the curvature functions. © 2015, Walailak University. All Rights Reserved.
Keywords: Curvature; Curve; Frenet frame; M-curvature functions; Null cone